THE IMPLEMENTATION OF INTERCULTURAL LANGUAGE LEARNING IN AN EFL CLASSROOM : A Descriptive Study at a State University in West Java - Miftakh, Fauzi (2016)
The purpose of this study was to discover how intercultural language learning was implemented at the sixth semester students of the English Education Department at a state university in West Java and also to find out the students' responses to learning English with intercultural language learning. This study was designed as a descriptive qualitative study that was conducted in six meetings of a half semester of 2014/2015 academic year that involved 31 participants. The qualitative data were collected through classroom observations, questionnaire and interviews. Based on the findings in the classroom observations, it was showed that the intercultural language learning had been implemented properly and effectively with a greater involvement by the teacher and the students. The teacher frequently implemented the elaborations of the five principles of intercultural language learning in every meeting even though there were some activities that were not implemented in some meetings. In addition, based on the findings from the questionnaire and interviews, the students gave positive responses to the implementation of intercultural language learning and they showed a greater interest in participating in the course. The intercultural language learning also proved that the students were given the opportunity to become intercultural speakers either during the teaching and learning process or in their daily life. Finally, it is recommended that the intercultural approach should be implemented by other English teachers in any subject and at all levels of students. Keywords: Interculural language learning, intercultural competence, English as a Foreign Language, students' attitudes.